Participa??o Social no Conselho Regional de Desenvolvimento Rural Sustent?vel ? CODES do Territ?rio de Identidade Bacia do Jacu?pe, Semi?rido Baiano (2005-2015) - Rios, Joilma Reis (2016)
The search for the country-boosted control over time Brazilian governments to adopt various forms of division, whether political, geographical, economic, social and/or administrative nature. Among these dozens of formats, this work focuses on the Identity Territories (ITs) adopted in 2007 by the Government of Bahia as planning units. Specifically, it aims to understand the role of Regional Sustainable Rural Development Council of the Bacia do Jacu?pe Identity Territory (CODES Bacia do Jacu?pe) in creating spaces and tools that enable citizen participation in the process of public policies to promote Territorial Development sustainable for this portion of the semi-arid of Bahia. Therefore, discusses the concepts wrapped in issues of Public Policy, Development, Social Participation and Territory. It describes the role of social organizations in the historical process of a decade (2005-2015) CODES Bacia do Jacu?pe and what level of autonomy of this body with the state. For the methodological aspect, we used the bibliographical and documentary research, as well as semi-structured interviews to enter the research object space, in order to reveal the panorama of social situations, geographical, political, economic and historical municipalities that make up the IT Bacia do Jacu?pe. The study revealed that, despite being an improvement in the context of public policy, the adoption of Identity Territories denotes a weakness in relation to deliberative action CODES Bacia do Jacu?pe, in view of the remnants of an archaic and undemocratic political system, reaffirmed in the consolidation of the State, based on the maintenance of spatial domain, in the interests of a new elite.